Ultrasonography versus low-dose computed tomography in diagnosis and size measurement of urolithiasis - Gharti, Resham; Thapa, Madan; Thapa, Subash; Lamichhane, Sandesh (Journal of Chitwan Medical College, 2025)
Introduction: Urolithiasis poses significant global health challenges. This study evaluates ultrasonography versus low-dose CT in diagnosing urinary tract stones. Method: This prospective comparative study was conducted at the Radiology Department of Universal College of Medical Sciences Teaching Hospital (UCMS-TH), Bhairahawa, Nepal from Sep 2021 to Mar 2023. Ethical approval was obtained. Adult patients with suspected urolithiasis referred for imaging who had both ultrasound (USG) and non-contrast computed tomography (NCCT) KUB within one-week were included. Sample estimation was done by Buderer’s formula for expected sensitivity/specificity. Patients with interventions or spontaneous stone passage between investigations, pregnancy were excluded. Analysis was performed using IBM SPSS 20 to compare accuracy of USG to NCCT for urolithiasis by calculating sensitivity, specificity. Chi-square test was performed, statistical significance set at p<0.05. Result: Out of 160 urolithiasis patients, males were 88(55%), mean age 39.29 years (SD=13.73), mean BMI of 23.82 (SD=2.12), stone size on USG 7.12 mm (SD=6.15) and on CT 7.63 mm (SD=5.56). Accuracy for detecting stones was high by CT, sensitivity 96.1% compared to 44.9% by USG. The CT showed higher accuracy in detecting ureteral stones and small stones <3 mm. For larger stones of >9 mm both CT and USG were equally effective. Statistically significant differences (p<0.001) were noted for localization and size of stones favouring CT. Conclusion: This study found that CT was superior than USG in detecting urolithiasis, particularly small stones and ureteral calculi, highlighting higher sensitivity and accuracy of CT as a diagnostic tool for urinary stones.